Frictional resistance to sliding archwires with repeated displacement - Liew C.F; Brockhurst P.; Freer T.J (Sciendo, 2002)
Frictional resistance between a length of stainless steel archwire and a single bracket was calculated, and the effects of cyclical displacement forces on frictional resistance were tested. With the application of repeated displacement forces to the archwire, the force required to slide the wire through the bracket was substantially reduced. The percentage reduction in the force required to slide the wire was dependent on the size of the displacement force applied to the archwire. Frictional resistance in the mouth may not be satisfactorily reflected by steady mode laboratory models. The clinical implications for different types of orthodontic brackets remain unresolved.